Mnemonic diplomacy in Russian-Serbian relations: The limits of the possible - A. M. Ponamareva (Вестник Московского Университета. Серия XXV: Международные отношения и мировая политика)
The Balkan region has traditionally been of particular importance for Russia, and currently Serbia remains one of the few European countries potentially exposed, due to ideological affinity, to the influence of Russia’s soft power. Memory policy is an important tool in creating and maintaining this affinity because it enables formulation of unifying historical narratives and shared vision of the key events in the common history, thereby providing underpinning for assessments of current developments and for creating an image of the desired future. However, it has its limits and boundaries, and this paper aims at assessing the strength of the Russian-Serbian mnemonic union. The research builds on the concept of ‘mnemonic diplomacy’, which refers to a set of techniques and methods for the affirmation, coordination and dissemination of certain historical narratives designed to support the state’s foreign policy activities. The author argues that the Russian-Serbian memory alliance is based primarily on common assessments of the events of World War II. The paper examines the key stages, internal and external drivers of this mnemonic union development, as well as identifies contradictions and conflicts inherent to this process. The author emphasizes that within the framework of the Russian-Serbian memory alliance both parties have always pursued their own goals. For instance, Serbia sought to use it to increase its weight in the Balkan and, more broadly, European politics, as well as to strengthen relations with its traditional geopolitical ally. For Russia, this mnemonic alliance acquired particular significance when the country’s leaders set a course for transforming the post-Cold War world order. However, it was exactly this new turn of Russia’s foreign policy whose most visible manifestation was the launch of the special military operation in Ukraine that dramatically complicated Serbia’s position, including that in the field of memory politics. At the same time it has revealed the limits of the Russian-Serbian mnemonic union. The author concludes that the effectiveness of mnemonic diplomacy and, more broadly, the very possibility of forming and maintaining mnemonic alliances, ultimately depend on a combination of objective factors, including close economic ties and mutual geopolitical interest. Pushed outside this comfort zone, complementary historical narratives built solely on the appeal to the common heritage quickly lose their power of attraction.